Factors Influencing Rice Production and The Relationship With Fertilizer Subsidies at East OKU District - Farado, C; Munajat, Munajat; fifi, Fifian Permata Sari; Tarmizi, A (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2024)
East OKU Regency, renowned for its vast potential in the primary agricultural and plantation sectors, has witnessed a significant increase in agricultural production. However, many farmers report difficulties in obtaining subsidized fertilizer, which hampers optimal planting processes. This research aims to analyze the factors affecting rice production and the impact of subsidized fertilizer in Madang Suku I District, East OKU Regency. The research employs a survey method and uses simple random sampling for data collection. Multiple regression analysis is utilized to analyze the data. The study examines the impact of subsidized fertilizers, specifically urea fertilizer (X1) and NPK fertilizer (X2), both individually and collectively, on rice production in Madang Suku I District, East OKU Regency. The findings reveal that the subsidized fertilizer policy significantly contributes to increased rice production in the region. Rice production in East OKU has reached 689,678 tons of milled dry grain (GKG) or 811,385 tons of unmilled dry grain (GKP) from a planting area of 108,141 hectares (Ha), marking a 20 percent increase compared to 2021. Consequently, in early 2022, East OKU Regency emerged as one of the top rice-producing districts in South Sumatra province. Several factors influence rice production in Madang Suku I District, including land area, labor, the number of seeds, subsidized fertilizer, and pesticides. The land area has the most significant impact on rice production, with a beta coefficient of 0.567, indicating its substantial influence.